Alkali Metal complexes: Mixed Ligand Complexes of Alkali Metal salts of Picolinic acids, Quinaldinic acid and their N-Oxides with 1, 10-Phenanthroline Mono-N-Oxide - Prakash, D.; Prasad, S.S.; Chandra, R.; Gupta, O.P. (Asian Journal of Chemistry, 2010)
Complexes having the general formula ML. L´ where M = Li, Na and K, HL = picolinic acid, quinaldinic acid and their N-oxides and L´ = 1,10- phenanthroline mono-N-oxide have been synthesized. Complexes have been characterised on the basis of elemental analysis, IR spectral studies and conductivity measurements.